Political and public acceptability of a sugar-sweetened beverages tax: a mixed-method systematic review and meta-analysis - Michelle Eykelenboom; Maartje M. van Stralen; Margreet R. Olthof; Linda J. Schoonmade; Ingrid H. M. Steenhuis; Carry M. Renders; on behalf of the PEN Consortium (BMC, 2019)
Abstract Background Taxation of sugar-sweetened beverages (SSBs), as a component of a comprehensive strategy, has emerged as an apparent effective intervention to counteract the rising prevalence of overweight and obesity. Insight into the political and public acceptability may help adoption and implementation in countries with governments that are considering an SSBs tax. Hence, we aimed to conduct a systematic review and meta-analysis to synthesize the existing qualitative and quantitative literature on political and public acceptability of an SSBs tax. Methods Four electronic databases (PubMed, Embase, Scopus, Web of Science) were searched until November 2018. The methodological quality of the included studies was assessed using the Mixed Methods Appraisal Tool. Qualitative studies were analyzed using a thematic synthesis. Quantitative studies were analyzed using a random-effects meta-analysis for the pooling of proportions. Results Thirty-seven articles reporting on forty studies were eligible for inclusion. Five themes derived from the thematic synthesis: (i) beliefs about effectiveness and cost-effectiveness, (ii) appropriateness, (iii) economic and socioeconomic benefit, (iv) policy adoption and implementation, and (v) public mistrust of the industry, government and public health experts. Results of the meta-analysis indicated that of the public 42% (95% CI = 0.38-0.47) supports an SSBs tax, 39% (0.29-0.50) supports an SSBs tax as a strategy to reduce obesity, and 66% (0.60-0.72) supports an SSBs tax if revenue is used for health initiatives. Conclusions Beliefs about effectiveness and cost-effectiveness, appropriateness, economic and socioeconomic benefit, policy adoption and implementation, and public mistrust of the industry, government and public health experts have important implications for the political and public acceptability of an SSBs tax. We provide recommendations to increase acceptability and enhance successful adoption and implementation of an SSBs tax: (i) address inconsistencies between identified beliefs and scientific literature, (ii) use raised revenue for health initiatives, (iii) communicate transparently about the true purpose of the tax, and (iv) generate political priority for solutions to the challenges to implementation.